2021
DOI: 10.1093/ijnp/pyab012
|View full text |Cite
|
Sign up to set email alerts
|

Perception-Action Integration Is Modulated by the Catecholaminergic System Depending on Learning Experience

Abstract: Background The process underlying the integration of perception and action is a focal topic in neuroscientific research and cognitive frameworks such as the “Theory of Event Coding (TEC)” have been developed to explain the mechanisms of perception-action integration. The neurobiological underpinnings are poorly understood. While it has been suggested that the catecholaminergic system may play a role, there are opposing predictions regarding the effects of catecholamines on perception-action i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…However, considering that atVNS may unfold its effect on cognitive control processes via the modulation of gain control processes, it is crucial to keep in mind that such processes are also central for learning and plasticity processes ( Dosher and Lu, 1998 ; Gold et al, 1999 ). Several pharmacological studies targeting the NE system have shown that effects of the pharmacological stimulation can be modulated by prior experience (learning) with the task at hand to examined cognitive control ( Bensmann et al, 2019 ; Mückschel et al, 2020a , 2020b ; Eggert et al, 2021 ). Interestingly, it has been shown that prior task experience can eliminate effects of catecholaminergic modulations in cognitive control contexts ( Mückschel et al, 2020b ) and even reverse intended expected cognitive enhancement effects of catecholaminergic modulation ( Mückschel et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…However, considering that atVNS may unfold its effect on cognitive control processes via the modulation of gain control processes, it is crucial to keep in mind that such processes are also central for learning and plasticity processes ( Dosher and Lu, 1998 ; Gold et al, 1999 ). Several pharmacological studies targeting the NE system have shown that effects of the pharmacological stimulation can be modulated by prior experience (learning) with the task at hand to examined cognitive control ( Bensmann et al, 2019 ; Mückschel et al, 2020a , 2020b ; Eggert et al, 2021 ). Interestingly, it has been shown that prior task experience can eliminate effects of catecholaminergic modulations in cognitive control contexts ( Mückschel et al, 2020b ) and even reverse intended expected cognitive enhancement effects of catecholaminergic modulation ( Mückschel et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…An underlying common mechanism might refer to “gain control” processes, which improves the overall signal-to-noise ratio when gain is high ( Aston-Jones and Cohen, 2005 ; Ferguson and Cardin, 2020 ). Both theta oscillations and the catecholaminergic system improve gain control functions ( Servan-Schreiber et al., 1990 ; Aston-Jones and Cohen, 2005 ; Ponjavic-Conte et al., 2012 ; Warren et al., 2016 ; Adelhöfer et al., 2019 ; Eggert et al., 2021 ). Given the interaction of differences in the theta frequency band and the manipulation of the catecholaminergic system, it is likely that both factors may be expressions of the same processes ( Adelhöfer et al., 2019 ; Chen et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Catecholamines are associated among others with impulse control ( Hershey et al., 2004 ; Chambers et al., 2009 ; Willemssen et al., 2009 ; Aron, 2011 ; Badgaiyan and Wack, 2011 ; Ghahremani et al., 2012 ; Bari and Robbins, 2013 ). Catecholaminergic neural transmission can be modulated by methylphenidate (MPH) ( Linssen et al., 2014 ; Bensmann et al., 2019 ; Mückschel et al., 2020 ; Eggert et al., 2021 ). MPH acts as a catecholamine reuptake inhibitor, thereby increasing the concentration of dopamine and norepinephrine in the synaptic cleft ( Ramos and Arnsten, 2007 ; Iversen et al., 2009 ; Walitza et al., 2016 ; Xing et al., 2016 ; Faraone, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Please refer to the Method section for further information regarding the timing, etc. Adopted from Eggert et al 25 . …”
Section: Methodsmentioning
confidence: 99%